IMPLEMENTASI PROPHETIC PARENTING OLEH ORANG TUA ANAK KELOMPOK B DI KB/TK PAS AULAADUL YAMIN - Nur Rahmatika Utari; Marmawi R; Lukmanulhakim Lukmanulhakim (Universitas Tanjungpura, 2022)
This research aims to determine the implementation of prophetic parenting by parents in KB/TK PAS Auladul Yamin Southeast Pontianak. The implementation of prophetic parenting includes showing a good attitude, choosing the right time to advise, being fair, fulfilling children’s rights, giving chindren toys or gifts, helping children be filial and obedient, and giving punishment. This research had 48 parents from Group B as participants. This study employed open questionnaire techniques and documentation to obtain data. The data used in this study came from an open questionnaire distributed to parents and documentation in the form of an open questionnaire document. According to the results of this study, parents in Group B used prophetic parenting to educate their children.